Factors Associated with FMT Failure in Clostridioides difficile Infection and Age-Related Considerations: A Review - Irgi, Khaeru; Kasasiah, Ahsanal; Rusmayanti, Agustina (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Clostridioides difficile infection (CDI) is a major cause of nosocomial diarrhea worldwide, and limitations of standard antibiotic therapy have driven the adoption of fecal microbiota transplantation (FMT) as an alternative therapeutic approach. Although FMT achieves clinical success in most patients, treatment failure still occurs in a considerable proportion of cases. Existing literature has examined overall FMT efficacy, yet no review has comprehensively synthesized the multifactorial determinants of FMT failure while incorporating age-related considerations. This narrative review provides an integrative overview of factors contributing to FMT failure in adults with CDI. A literature search of PubMed and Google Scholar identified original research articles published between 2015 and 2025. Evidence indicates that FMT failure is influenced by host-related factors such as comorbidities, immune function, and nutritional status; disease-related characteristics, including CDI severity and recurrence history; technical aspects, such as bowel preparation, donor type, and route of administration; and pharmacological factors, including antibiotic exposure before or after the procedure. These factors collectively affect donor microbiota engraftment and increase the risk of therapeutic failure. Age-related physiological and microbiome changes may additionally modify treatment responses. This review highlights the need for comprehensive patient assessment, standardized procedural protocols, and careful post-FMT monitoring. Addressing current evidence gaps and improving clinical guidance will be essential for optimizing the safety and effectiveness of FMT across different adult age groups.